Analisis pengaruh Kepercayaan, Servicecape dan Komunikasi terhadap kepuasan pasien pada Rumah Sakit (RSUP Prof. Dr. R.D. Kandou Manado - Siwi, Amaldo Reza (Universitas Sam Ratulangi, 2019)
This study aims to analyze the confidence of servicecape and communication on patient satisfaction at RSUP Prof. Dr. R.D. Kandou Manado. The population in this study was 37,498 patients inpatients. For the five most poly patients who stayed were Poly Public Health, Internal Medicine, Surgery, Child Health and Cardiology. Data is analyzed using research data processing techniques using SPSS 22. From the results of the study obtained findings that trust, servicecape, and communication have a significant effect on patient satisfaction simultaneously. Servicecape for patient satisfaction does not significantly influence patient satisfaction partiallyKeywords: Trust, Scape Service, Communication and Customer Satisfaction